A comparison between aggression and self-esteem among Universiti Teknologi MARA (UiTM) Shah Alam athletes / Mohad Anizu Mohd Nor ...[et al.] - Mohd Nor, Mohad Anizu; Parnabas, Vincent; Shaharudin, Mohamad Azuwan; Ab Rahman, Zarizi; Roper, Alexander Paul (Universiti Teknologi MARA, 2020)
Human aggression was a major worldwide health issue that brings negative effect to victims, perpetrators, and society. One of the areas that may be potentially variables for understanding aggression was self-esteem that could influence whether someone display an aggressive behaviour. Therefore, the aim of this study was to determine the relationship between the level of aggression and level of self-esteem among Universiti Teknologi MARA (UiTM) Shah Alam student-athletes. This study was very important to determine the athlete's aggression and selfesteem level based on the differences of genders and types of sport. Furthermore, the findings of this study may help in promoting a beneficial knowledge among coaches and athletes about aggression level and also self-esteem level toward maintaining and improving sports performance. A correlational study was selected in order to conduct this study. This correlational study was selected because this study was closely related to both descriptive and causalcomparative research. The instrument used for this study comprised of a 10-item Rosenberg SelfEsteem Scale (RSES) and 19-item of Aggression Questionnaire (AQ), which had been distributed in UiTM Shah Alam. The samples consisted of 260 UiTM Shah Alam athletes, included male and female, individual and team sports, age ranged between 18 until 26 years old. Independent t-test showed there was no significant difference between genders and types of sport on aggression level, p > 0.05. Result also showed that there was no significant difference on self-esteem between types of sport, p > 0.05. Meanwhile, a result found that there was a significant difference on selfesteem between genders, p < 0.05. Result also showed that there was a positive correlation between aggression and self-esteem among UiTM Shah Alam athletes, (r = 0.20, p < 0.05). Present findings indicated that athletes who had higher aggression level tend to have a higher level of self-esteem. Therefore, psychological skill training (PST) recommended as a better coping technique in order to promote better adaptation to the constraints of the sports involvement.